Which empowerment, which Health Promotion?Conceptual convergences and divergences in preventive health practices - Marcos Santos Ferreira; Luis David Castiel
Based on the multiple meanings, "empowerment" can be identified with either conservative or critical Health Promotion approaches. From a conservative approach, the concept is viewed as an essentially individual phenomenon, centered on the provision of information and the external transfer of power in the name of the collective good. From this approach, the relationship between "psychological" and "community" empowerment is not considered. From a critical approach, the concept is viewed as a relational phenomenon that manifests itself in the dialectic conflict of interests between individuals, groups, and social classes. From this approach, "psychological" and "community" empowerment are seen as micro and macro levels of analysis, and social transformations are the result of simultaneous changes at these levels. The use of the notion of empowerment without critical reflection or political analysis of power relations in society disseminates vague, romantic, and homogeneous views of "community". Therefore, to assume the relational nature of empowerment means to accept its interdependence with the notion of participation, without which there can be no social transformation. Thus, one should be vigilant about multiple meanings that empowerment can given in Health Promotion discourse.